Comparison of two methods for collecting antibiotic use data on small dairy farms. - Redding, L.E. (2014)
Antibiotics are commonly used in animal agriculture; they can improve animal health and productivity, but their use may also represent a public health threat. Very little is known about antibiotic use on small farms in lower/middle income countries. To understand antibiotic use on these farms and promote the judicious use of these drugs, pharmacoepidemiologic data are necessary. However, acquiring such data can be difficult, as farmers are often illiterate (and therefore cannot participate in written surveys or keep treatment records), antibiotics can be obtained over-the-counter (in which case no prescriptions are generated) and monitoring and surveillance systems for drug use are often non-existent. The goal of this study was to compare two methods of acquiring pharmacoepidemiologic data pertaining to antibiotics that are well-adapted to farms in lower-middle income countries: self-report and the collection of discarded drug packaging. A convenience sample of 20 farmers in Cajamarca, Peru, participated in the study. Farmers placed discarded antibiotic packaging in bins for six months. At the end of the six-month period, farmers were interviewed and asked to recall the antibiotic usage that occurred on their farm over the past month and past six months; these self-reported data were quantitatively and qualitatively compared to the bin contents collected in the last month and previous six months. We found that the agreement between the bins and self-report was relatively poor for both the quantity and types of antibiotics used. The bins appeared to perform better than self-report when bottles and mLs of antibiotics were measured, while self-report appeared to perform better for intra-mammary infusions. The bins also appeared to perform better when data pertaining to an extended time period (six months) were collected. The results of this study will provide guidance to investigators seeking to collect pharmacoepidemiologic data in similar environments.